Atopic dermatitis and attention‐deficit/hyperactivity disorder comorbidity in children and adolescents: Epidemiology, mechanisms, and clinical management - Qingyang Zhao; Yuan Liang; Ying Liu; Chunping Shen; Mutong Zhao; Jing Tian; Lei Jiao; Jing Sun; Ying Gu; Qiong Wu; Shan Wang; Lin Ma (Pediatric Investigation, 2026)
ABSTRACT Atopic dermatitis (AD) and attention‐deficit/hyperactivity disorder (ADHD) frequently co‐occur in children and adolescents, increasing the disease burden and clinical complexity. Accumulating evidence suggests that children with AD have a higher risk of incident ADHD, a risk that is particularly pronounced in those with early‐onset, severe AD, or significant sleep disturbances. The underlying mechanisms are hypothesized to involve the dysregulation of the “inflammation–itching–neurobehavioral” axis. This narrative review synthesizes current evidence regarding the epidemiology, potential mechanisms, and clinical management of this comorbidity. We propose that proactive screening and aggressive control of skin inflammation and pruritus are key to disrupting this vicious cycle.